FISCALITE CONGOLAISE FACE A LA THEORIE D’ARTHUR LAFFER - AIME, BITEGETSIMANA; Jackson, RUKUNDO (IJRDO - Journal of Business Management, 2022)
As part of this work, it was question of talking about the effects of taxation on economic activities in DRC. . This study is crystallized on the theory of Arthur Laffer that states : “too much tax kills the tax”. This theory shows that the tax must be invisible to say that it should not be heavy on the fear of operators to discourage them, but rather apply an optimal rate. In addition, the economist was looking for demonstrate the limit of the efficiency of income taxation. Under a certain threshold, the state deprives money that he could perceive. Indeed, a tax rate of zero percent will not renounce the public trunks. However, after a certain threshold, we would discourage the work and creation of wealth while the evasion and tax avoidance would be discouraged. The tax base would be significantly reduced. So it would sometimes be a timely to reduce the tax to grow the tax revenues of the state. The results found show a negative impact of a decrease in economic activities of 0,9651768 due to increased taxes of 1 percent.